Exploring the usage of #Kerajaan Gagal by Twitter users during COVID-19 - Mohd Nuzulrudin, Nurul Ayuni; Ibnu, Ireena Nasiha; Yaccob, Yasmin (Qualitative Research Association of Malaysia, 2024)
Social media has become the preferred political communication tool whereby it has been used to influence public political perception and act as a platform for political discourse. During the COVID-19 pandemic, people expressed their opinions on the ruling government through trending hashtags. This study explores the role of the political hashtag #KerajaanGagal in affecting public perception of the government and how public debate on social media is influenced by the political conflict in Malaysia. The study aims to examine how the usage of the political hashtag #KerajaanGagal on social media influences the public perception and opinion towards the then Prime Minister, Tan Sri Muhyiddin’s government. Qualitative research methodology was adopted in this study by conducting in-depth interviews with ten informants among Twitter users who are opinion leaders, activists, social media and political analysts, all of whom are between millennial age groups. Key outcomes of the trending political hashtag #KerajaanGagal were found to defy the ‘Spiral of Silence Theory’ that individuals tend to selfcensor their opinions to fit in with the perceived majority. The catchy #KerajaanGagal hashtag reflects a relatable current situation, gaining public attention. The usage and further trending of #KerajaanGagal is found to be due to public dissatisfaction and frustrations during the COVID-19 pandemic and Movement Control Order (MCO) coupled with the lack of engagement or response from the targeted party. Social media is able to transform the political scene as it enables the public to practice freedom of speech and ‘find’ like-minded people to align themselves in support of a cause.